SISTEM INFORMASI SANGGAR TARI HERITAGE UNIVERSITAS UBUDIYAH INDONESIA BERBASIS WEB - Elvidana, Syatta (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2014)
The development of technology always push the man to continue to bring new innovations in managinginformation, Dance sanggarubudiyahindonesia heritage is a place for college students creativity universityubudiyahindonesia .Founded in 2013 under the guidance of head of ubudiyah . Dancesanggarubudiyahindonesia heritage had participated in various events , as the local , national andinternational events . Dance studio ubudiyah heritage university of indonesia in terms of the system will stilluse manual way so that the system formed not effective and efficient . One is administrative manageactivities sanggar. The type of activity administration was the acceptance of new , the management ofparticipants , instructors , class , material , the schedule , and other activities still manually operated withoutthe help of a computer devices out there .These information systems use technology web application assistedby using a methodology waterfall iterative this model to approach and systematically serial start of the levelof the needs of the system and heading to the stage of analysis , the design , as well , testing and verification ,and maintenance . This model helped the performance of the management of studios and studio in managingthe administration also providing facilities to instructors and participants to get information about thetimetable studio , the report and the value of presence , studios and other information related activitiesKeyword: information technology, sanggar dance, web-based